Autophagy-augmenting peptide nanoplatform for synergistic chemo-immunotherapy against breast cancer - Chen Wei; Wei Gao; Xingyue Li; Ming Fu; Fantao Lin; Xiaoyu Zhao; Huiying Jia; Kang Zhang; Changgang Sun; Rui Wang; Jingkun Bai (Chemical Engineering Journal, 2026)

Microbial-mediated soil carbon accrual under 12-year reduced nitrogen fertilisation and intercropping - Kepan Yang; Yali Liu; Chaoqun Zou; Jianghao Tan; Huiying Lin; Lei Liu; Xiting Zhang; Enqing Hou (Agriculture, Ecosystems & Environment, 2026)

RNA-binding protein TARDBP enhances NPTX1 stability to induce neuronal injury and diabetic cognitive impairment - GuiTing Liu; XiaoXuan Qi; SiOu Li; XinPing Wang; TingYuan Han; LingJia Cui; HuiYing Yue; Feng Liu; Ying Lin (Molecular & Cellular Toxicology, 2026)

VcNADP-ME4 positively regulates malic acid degradation in blueberry fruit as modulated by two bZIPs - Yongfang Dai; Yi Min; Yuxin Leng; Miao Zhou; Huiying Chong; Lei Peng; Xiaoya Zheng; Lin Wang; Guangqin Wen; Xiaopeng Wen (Journal of Plant Physiology, 2026)

A membrane-mediated algal–bacterial coupling strategy for energy – efficient and low-carbon PHA production - Long Huang; Lin Liu; Guangyi Zhang; Guoqiang Li; Yingke Fang; Yuan Li; Huiying Yang; Hongbin Xu (Bioresource Technology, 2026)

Unraveling the impacts of blue-green-gray landscape patterns on PM2.5 in high-density urban areas: A case study of Xi’an - Baojun Yang; Lin Zhang; Danchen Yang; HuiYing Ma; Haifan Xie; Jiahui Hou; Ling Qiu; Tian Gao (Atmospheric Pollution Research, 2026)

Incentive-responsive energy use in low-income housing: Evidence from Hong Kong public rental estates - Huiying (Cynthia) Hou; Yung Yau; Ka Kiu Law; Minqi Lin (Energy and Buildings, 2026)

Unexpected seasonal variability of Hedley-occluded phosphorus in phosphorus-supplied subtropical forest soils - Huiying Lin; Xianzhen Luo; Julian Helfenstein; Zhaofeng Chang; Zhimin Li; Huijun Ye; Yongbiao Lin; Guodong Yuan; Enqing Hou (CATENA, 2025)

Development of an interpretable machine-learning model for capturing nonlinear dynamics of multisensory interactions in public open spaces - Minqi Lin; Chi Kwan Chau; Huiying (Cynthia) Hou; Shiu Keung Tang (Building and Environment, 2025)

Comparison of Reflectivity Consistency between Spaceborne Precipitation Radar and Ground-based Weather Radar in China and the United States - Peng Chen; Lin Chen; Gang Wang; Qiong Wu; Huiying Wang; Peng Zhang (Advances in Atmospheric Sciences, 2025)

Oat (Avena sativa L.) fermented by GRAS-grade microorganisms: From improvement of the quality properity and health benefits, safety assessment to potential industrial applications - Huiying Lin; Tao Fei; Xiaoze Liu; Xue Lin; Lu Wang (Trends in Food Science & Technology, 2025)

Vertical distribution of microplastics in coastal sediments of Xuwen Coral Reef National Nature Reserve, China - Mayakrishnan Machendiranathan; Guangzhe Jin; Huaxia Huang; Tingbang Liang; Zongxuan Lin; Huiying Lin; Lingling Xie; Fajin Chen (Journal of Oceanology and Limnology, 2025)

Novel solid-phase extraction promotes simultaneous colloidal gold immunochromatographic assay of malachite green, leuco-malachite green, chloramphenicol, and semi-carbazone metabolites in aquatic products - He Ziyang; Zhang Shaoen; Chen Qingzhou; Lin Hong; Sui Jianxin; Wang Kaiqiang; Wang Huiying; Cao Limin (Food Chemistry, 2025)

Unlocking the potential of Cupriavidus necator H16 as a platform for bioproducts production from carbon dioxide - Yuheng Wang; Lin Cui; Lijuan Ding; Xiaoyun Su; Huiying Luo; Huoqing Huang; Yuan Wang; Bin Yao; Jie Zhang; Xiaolu Wang (World Journal of Microbiology and Biotechnology, 2024)

Novel Pathogenic Mutation of P209L in TRPC6 Gene Causes Adult Focal Segmental Glomerulosclerosis - Tianxi Yu; Yongqiang Ji; Xin Cui; Ning Liang; Shuang Wu; Chongjun Xiang; Yue Li; Huiying Tao; Yaqi Xie; Hongwei Zuo; Wenting Wang; Nauman Khan; et al. (Biochemical Genetics, 2024)

One-stone-for-two-birds strategy to achieve effective electrochemical nitrate reduction towards ammonia synthesis with Ru doped cobalt tungstate - Xue Bai; Keyu Zhou; Lan Lin; Huiying Li; Qianggen Li; Guangyin Fan (Fuel, 2024)

On the transferability of residence time distributions in two 10-km long river sections with similar hydromorphic units - Jie Bao; Xuehang Song; Yunxiang Chen; Yilin Fang; Xinming Lin; Zhangshuan Hou; Zhuoran Duan; Huiying Ren; William Perkins; Xiaoliang He; Timothy Scheibe (Journal of Hydrology, 2024)

The association between PM2.5 components and blood pressure changes in late pregnancy: A combined analysis of traditional and machine learning models - Lijie Wang; Li Wen; Jianling Shen; Yi Wang; Qiannan Wei; Wenjie He; Xueting Liu; Peiyao Chen; Yan Jin; Dingli Yue; Yuhong Zhai; Huiying Mai; et al. (Environmental Research, 2024)

Seafood waste derived carbon nanomaterials for removal and detection of food safety hazards - Ziyang He; Hong Lin; Jianxin Sui; Kaiqiang Wang; Huiying Wang; Limin Cao (Science of The Total Environment, 2024)

Differential factors determine the response of soil P fractions to N deposition in wet and dry seasons in a subtropical Moso bamboo forest - Quanxin Zeng; Yuexin Fan; Qiufang Zhang; Xiaochun Yuan; Kaimiao Lin; Jiacong Zhou; Huiying Lin; Huan Xie; Juyan Cui; Yue Wu; Yuehmin Chen (Plant and Soil, 2024)

An enhanced monitoring method for spatio-temporal dynamics of salt marsh vegetation using google earth engine - Wenbin Yi; Nan Wang; Huiying Yu; Yinghui Jiang; Dong Zhang; Xinyang Li; Lin Lv; Zhenglei Xie (Estuarine, Coastal and Shelf Science, 2024)

Molecular cloning, expression, and functional analysis of a putative lectin from the pearl oyster (Pinctada fucata, Gould 1850) - Peng Liu; Wenyue Li; Yue Peng; Siyin Han; Zhongxiu Liang; Yanhui Cen; Xinrong Li; Peiyan Wang; Huiying Lv; Qingying Zhang; Honglin Chen; Jiang Lin (Fish & Shellfish Immunology, 2023)

Carbon dioxide flux and microbial responses under multiple-nutrient manipulations in a subtropical forest soil - Muhammed Mustapha Ibrahim; Zhimin Li; Huijun Ye; Zhaofeng Chang; Huiying Lin; Xianzhen Luo; Enqing Hou (Applied Soil Ecology, 2023)

Simultaneous qualitative and quantitative determination of 104 fat-soluble synthetic dyes in foods using disperse solid-phase extraction and UHPLC-Q-Orbitrap HRMS analysis - Ping Qi; Qingqiong Zhou; Guiyun Chen; Zihao Lin; Jinli Zhao; Huiying Xu; Hui Gao; Donghao Liu; Xinwu Mao (Food Chemistry, 2023)

Flooding dominates soil microbial carbon and phosphorus limitations in Poyang Lake wetland, China - Xingyun Huang; Yaxuan Li; Huiyin Lin; Xiuting Wen; Jie Liu; Zhifen Yuan; Chun Fu; Bofu Zheng; Leiqiang Gong; Huiying Zhan; Yu Ni; Yang Hu; et al. (CATENA, 2023)

A new model to accurately measure the radon exhalation rate from soil using AlphaGUARD - Shuaibin Liu; Tao Hu; Fen Lin; Zhongkai Fan; Ruomei Xie; Shuai Yuan; Jiulin Wu; Haibo Yi; Yixiang Mo; Jiale Sun; Linquan Chen; Huiying Li; et al. (Journal of Environmental Radioactivity, 2023)

First detection of tet(X4)-positive Enterobacterales in retail vegetables and clonal spread of Escherichia coli ST195 producing Tet(X4) in animals, foods, and humans across China and Thailand - Chao Yue; Xun Gao; Litao Lu; Yi-Yun Liu; Lu-Chao Lv; Xiaotong He; Guolong Gao; Yanxiang Jiao; Huiying Yue; Wannan Lin; Jian-Hua Liu (International Journal of Food Microbiology, 2023)

Predicting future well performance for environmental remediation design using deep learning - Xuehang Song; Huiying Ren; Zhangshuan Hou; Xinming Lin; Marinko Karanovic; Matt Tonkin; Vicky L. Freedman; Inci Demirkanli; Rob Mackley (Journal of Hydrology, 2023)

Testing machine learning algorithms on a binary classification phenological model - Wujun Dai; Huiying Jin; Lin Zhou; Tong Liu; Yuhong Zhang; Zhiqiang Zhou; Yongshuo H. Fu; Guangze Jin (Global Ecology and Biogeography, 2023)
Aim Phenological models have become a vital tool for predicting future phenological responses to global climate change. Recently, machine learning (ML) has been used successfully to develop phenological models based on ground observations. However, fitting an observation series that has been observed for only a few years (or even a decade) can easily lead to overfitting, and it is still a great challenge to predict future phenology accurately based on a short observation series. Here, based on historical ground phenological observations, we construct an ML‐based binary classification phenological model that can be applied to temperate trees. Innovation We thoroughly describe the construction process of a species‐specific ML‐based binary classification phenological model that is suitable for phenological predictions in both spring and autumn. Through experiments, we evaluate 18 commonly used ML classification algorithms and the effects of two parameters on the prediction performance of the model. Finally, we compare the performance between the binary classification model and six widely used ecophysiological models for accuracy of spring phenological prediction. Main conclusions The median root mean square error (RMSE) of the binary classification model for the first flowering date (93 observation series) was only 2.99 days, which proves that it is a good method of phenological prediction for temperate trees. This model can effectively overcome the insufficient sample size of ground observations for specific species and provide new insights of phenological predictions for tropical and subtropical trees. The comparison of different ML algorithms showed that the median root mean square errors of the six algorithms were 3.7 days) in prediction of spring phenology. In addition, this model can help us to infer plant physiological mechanisms and drivers of phenological change and provide more accurate predictions of plant phenological responses to climate change.

Effects of agricultural activities on hydrochemistry in the Shiyang River Basin, China - Wenhao Zhang; Guofeng Zhu; Dongdong Qiu; Yuwei Liu; Liyuan Sang; Xinrui Lin; Huiying Ma; Kailiang Zhao; Yuanxiao Xu (Environmental Science and Pollution Research, 2022)

Effects of nitrogen addition on the concentration and composition of soil-based dissolved organic matter in subtropical Pinus taiwanensis forests - Xiaochun Yuan; Juyan Cui; Kaimiao Lin; Cheng-Chung Liu; Jiacong Zhou; Qiufang Zhang; Quanxin Zeng; Lianzuan Wu; Yue Wu; Kongcan Mei; Huiying Lin; Huan Xie; et al. (Journal of Soils and Sediments, 2022)

Neuroprotective Effects of 2-Substituted 1, 3-Selenazole Amide Derivatives on Amyloid-Beta-Induced Toxicity in a Transgenic Caenorhabditis Elegans Model of Alzheimer’s Disease - Huiying Wang; Yuandong Yue; Haifeng Zhao; Hao Wu; Kai Jiang; Shuang Li; Meihua Zhao; Feng Lin (Neurotoxicity Research, 2021)

Inhibitory effects of novel 1,4-disubstituted 1,2,3-triazole compounds on quorum-sensing of P. aeruginosa PAO1 - Shuang Li; Yumin Zhang; Kai Jiang; Huiying Wang; Feng Lin (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Simulating warmer and drier climate increases root production but decreases root decomposition in an alpine grassland on the Tibetan plateau - Huiying Liu; Li Lin; Hao Wang; Zhenhua Zhang; Zijian Shangguan; Xiaojuan Feng; Jin-Sheng He (Plant and Soil, 2021)

Alpine grassland plants grow earlier and faster but biomass remains unchanged over 35 years of climate change - Hao Wang; Huiying Liu; Guangmin Cao; Zhiyuan Ma; Yikang Li; Fawei Zhang; Xia Zhao; Xinquan Zhao; Lin Jiang; Nathan J. Sanders; Aimée T. Classen; Jin‐Sheng He (Ecology Letters, 2020)
Satellite data indicate significant advancement in alpine spring phenology over decades of climate warming, but corresponding field evidence is scarce. It is also unknown whether this advancement results from an earlier shift of phenological events, or enhancement of plant growth under unchanged phenological pattern. By analyzing a 35‐year dataset of seasonal biomass dynamics of a Tibetan alpine grassland, we show that climate change promoted both earlier phenology and faster growth, without changing annual biomass production. Biomass production increased in spring due to a warming‐induced earlier onset of plant growth, but decreased in autumn due mainly to increased water stress. Plants grew faster but the fast‐growing period shortened during the mid‐growing season. These findings provide the first in situ evidence of long‐term changes in growth patterns in alpine grassland plant communities, and suggest that earlier phenology and faster growth will jointly contribute to plant growth in a warming climate.

Neurotoxicity of sodium salicylate to the spiral ganglion neurons: GABAA receptor regulates NMDA receptor by Fyn-dependent phosphorylation - Peiqiang Liu; Danxue Qin; Xi Huang; Huiying Chen; Wenhua Ye; Xiaoyu Lin; Jiping Su (Journal of Comparative Physiology A, 2019)

Salicylate-Induced Ototoxicity of Spiral Ganglion Neurons: Ca2+/CaMKII-Mediated Interaction Between NMDA Receptor and GABAA Receptor - Danxue Qin; Peiqiang Liu; Huiying Chen; Xi Huang; Wenhua Ye; Xiaoyu Lin; Fangyu Wei; Jiping Su (Neurotoxicity Research, 2019)

Clinical and molecular analysis of 6 Chinese patients with isoleucine metabolism defects: identification of 3 novel mutations in the HSD17B10 and ACAT1 gene - Ling Su; Xiuzhen Li; Ruizhu Lin; Huiying Sheng; Zhichun Feng; Li Liu (Metabolic Brain Disease, 2017)

Synthesis and evaluation of novel benzene-ethanol bearing 1,2,4-triazole derivatives as potential antimicrobial agents - Bochao Li; Dawei Zhang; Yumin Zhang; Dan Jiang; Shuang Li; Wei Lei; Huiying Wang; Feng Lin (Medicinal Chemistry Research, 2017)

Fingerprint analysis and multi-component determination of Zibu Piyin recipe by HPLC with DAD and Q-TOF/MS method - Hong Xiang; Huiying Xu; Libin Zhan; Lin Zhang (Natural Product Research, 2016)

CarHSFB2, a Class B Heat Shock Transcription Factor, Is Involved in Different Developmental Processes and Various Stress Responses in Chickpea (Cicer Arietinum L.) - Hao Ma; Chuntao Wang; Bin Yang; Huiying Cheng; Ze Wang; Abudoukeyumu Mijiti; Cai Ren; Guanghang Qu; Hua Zhang; Lin Ma (Plant Molecular Biology Reporter, 2016)

Orexins (hypocretins) contribute to fear and avoidance in rats exposed to a single episode of footshocks - Xiaoyu Chen; Huiying Wang; Zhang Lin; Sa Li; Yonghui Li; Hugo T. Bergen; Maria E. Vrontakis; Gilbert J. Kirouac (Brain Structure and Function, 2014)

WNT10A variants are associated with non-syndromic tooth agenesis in the general population - Shujuan Song; Ruiying Zhao; Huiying He; Jin Zhang; Hailan Feng; Liyun Lin (Human Genetics, 2014)